Robust Moving Horizon H∞ Control of Discrete Time-Delayed Systems with Interval Time-Varying Delays - Tascikaraoglu, F. Yjldjz; Kucukdemiral, I. B.; Imura, J. (HINDAWI LTD, 2014)
In this study, design of a delay-dependent type moving horizon state-feedback control (MHHC) is considered for a class of linear discrete-time system subject to time-varying state delays, norm-bounded uncertainties, and disturbances with bounded energies. The closed-loop robust stability and robust performance problems are considered to overcome the instability and poor disturbance rejection performance due to the existence of parametric uncertainties and time-delay appeared in the system dynamics. Utilizing a discrete-time Lyapunov-Krasovskii functional, some delay-dependent linear matrix inequality (LMI) based conditions are provided. It is shown that if one can find a feasible solution set for these LMI conditions iteratively at each step of run-time, then we can construct a control law which guarantees the closed-loop asymptotic stability, maximum disturbance rejection performance, and closed-loop dissipativity in view of the actuator limitations. Two numerical examples with simulations on a nominal and uncertain discrete-time, time-delayed systems, are presented at the end, in order to demonstrate the efficiency of the proposed method.
Keywords: MODEL-PREDICTIVE CONTROL; UNCERTAIN SYSTEMS; STATE; STABILITY; Engineering; Mathematics